2019
DOI: 10.1021/acscatal.9b00688
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Remote 1,n-Arylamination of Unactivated Terminal Alkenes

Abstract: A palladium-catalyzed remote 1,n-arylamination (from 1,3-to 1,11-arylamination) of unactivated terminal alkenes with aryl iodides and arylamines has been realized. This three-component reaction proceeded via Pd-catalyzed Heck arylation, alkene isomerization, and aza-Michael addition, exhibiting good regio-and chemoselectivity, and wide substrate scope. Preliminary mechanistic studies indicated that the in situ generated ortho/para-quinone methide intermediates served as the driving force for the alkene isomeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(21 citation statements)
references
References 84 publications
0
17
0
Order By: Relevance
“…Experimental results showed that the IMDA reaction of compound 7d that had no methylene unit between a 2-vinylphenyl group and a dienone group gave the fused compound 8d selectively, while the IMDA reaction of compounds 7e-g that had the one or two methylene units afforded bridged compounds 9e-g. In order to clarify the reason for the change of selectivity, density functional theory (DFT) calculations (B3LYP/6-31(d,p) or B3LYP/6-31G(d)) 32,33) of IMDA reactions of 7d, e, b, f were performed ( Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental results showed that the IMDA reaction of compound 7d that had no methylene unit between a 2-vinylphenyl group and a dienone group gave the fused compound 8d selectively, while the IMDA reaction of compounds 7e-g that had the one or two methylene units afforded bridged compounds 9e-g. In order to clarify the reason for the change of selectivity, density functional theory (DFT) calculations (B3LYP/6-31(d,p) or B3LYP/6-31G(d)) 32,33) of IMDA reactions of 7d, e, b, f were performed ( Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Compounds 6b,c were prepared by the reported method. 34) Synthesis of 2-(2-Vinylphenyl)phenol (6d) 35) To a cooled suspension of methyltriphenylphosphonium iodide (128 mg, 0.318 mmol) in tetrahydrofuran (THF) (3 mL) at 0 °C was added potassium tert-butoxide (56 mg, 0.50 mmol) under nitrogen. After 30 min, 6H-benzo[c] chromen-6-one 36) (25 mg, 0.15 mmol) which was prepared from phenyl 2-bromobenzoate was added.…”
Section: Methodsmentioning
confidence: 99%
“…In 2019, Lin, Yao et al. reported a Pd‐catalyzed three‐component coupling of unactivated terminal alkenes ( 119 ) with aryl iodides and arylamines, which allowed an efficient 1, n ‐arylamination ( n =3–11; Scheme ) . Both 2‐phenol‐and 4‐phenol‐substituted alkenes with different carbon‐chain lengths reacted smoothly to provide the corresponding products ( 122 ) in good yields with high regio‐ and chemoselectivities.…”
Section: Palladium Catalysismentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13][14] In comparison, intermolecular arylamination providing access to arylethylamine-based acyclic molecules is particularly di cult and remain rare, owing to their high entropic cost and the problems of controlling the chemoselectivity of multicomponent reactions. [15][16][17][18][19][20] The arylethylamine scaffold existed in many bioactive molecules and pharmaceuticals, such as dopamine agonists. [21][22] Only a few methods have been reported for the synthesis of this important motif via 1,2/2,1-arylamination of alkenes.…”
Section: Introductionmentioning
confidence: 99%